Mental health provision in schools: priority, facilitators and barriers in 10 European countries. Issue 3 (27th April 2016) - Patalay, Praveetha; Giese, Laura; Stanković, Miloš; Curtin, Catriona; Moltrecht, Bettina; Gondek, Dawid
Abstract : Background: Although schools are a key setting for the provision of mental health support for young people, little is known about the facilitators and barriers for providing such support. This study aimed to collect information from schools in 10 European countries regarding the priority given to mental health support for students, existence of a mental health‐related school policy, links with relevant external agencies, schools' perceptions on whether they are providing sufficient mental health support and the barriers to provision of mental health support. Methods: Data from 1346 schools were collected in France, Germany, Ireland, the Netherlands, Poland, Serbia, Spain, Sweden, United Kingdom and Ukraine through an online survey. Results: Around 3% of the surveyed schools indicated that mental health provision was not a priority, compared to 47% indicating that it was a high/essential priority. More than half the surveyed schools did not implement a school policy regarding mental health. Half the surveyed schools reported not providing sufficient support with the key barriers identified including limited staff capacity, funding, access to specialists and lack of national policy and less than a third of schools reported good or excellent links with local mental health services. However, the responses varied by country with 8–19% between‐country variation across the study outcomes. Secondary schools reported significantly better links with agencies, were more likely to have a school policy and were less likely to indicate having sufficient existing support compared to primary schools. Privately funded schools reported that mental health support was a higher priority and identified less barriers to provision compared to publicly funded schools. Conclusions: This study provides an up‐to‐date and cross‐country insight into schools' perceptions regarding priority given to mental health support and the barriers they face in providing sufficient mental health and wellbeing support for their students. The cross‐country comparisons allow for a better understanding of the relationships between policy, practice and implementation and provide a platform for shared experiences and learning.